Autoantibodies to Malondialdehyde–Acetaldehyde Are Detected Prior to Rheumatoid Arthritis Diagnosis and After Other Disease Specific Autoantibodies. Issue 12 (15th October 2020) - Mikuls, Ted R.; Edison, Jess; Meeshaw, Elizabeth; Sayles, Harlan; England, Bryant R.; Duryee, Michael J.; Hunter, Carlos D.; Kelmenson, Lindsay B.; Kay Moss, Laura; Feser, Marie L.; Wagner, Brandie; Parish, Mark C.; et al.
Abstract : Objective: To examine serum autoantibodies to malondialdehyde–acetaldehyde (MAA) prior to rheumatoid arthritis (RA) diagnosis. Methods: Concentrations of anti‐MAA antibody isotypes, anti–cyclic citrullinated peptide 2 (anti–CCP‐2), and IgM rheumatoid factor (IgM‐RF) were evaluated before and after RA diagnosis in samples from cases (n = 214) and controls (n = 210). The timing of elevations in autoantibody concentrations relative to RA diagnosis was explored using separate mixed models for each antibody and/or isotype. Associations between prediagnosis autoantibody concentrations in RA patients were examined using mixed effects linear regression models. Results: Concentrations of IgG (log2 difference 0.34) and IgA (log2 difference 0.43) anti‐MAA antibodies in RA patients diverged from controls at 3.0 years and 2.3 years prior to diagnosis, respectively ( P < 0.05 for both). There was no evidence of case–control divergence for IgM anti‐MAA antibody concentration. Anti–CCP‐2 and IgM‐RF concentrations diverged between RA patients and controls beginning at 17.6 years and 7.2 years prior to RA diagnosis, respectively. All 3 anti‐MAA antibody isotypes (IgA, IgM, and IgG) were significantly associated with anti–CCP‐2 antibody and RF concentrations prior to diagnosis (β = 0.22–0.27 for IgM‐RF; β = 0.44–0.93 for anti–CCP‐2) ( P < 0.001). Conclusion: IgG and IgA anti‐MAA autoantibodies are elevated prior to RA diagnosis but appear later in the preclinical course than anti–CCP‐2 or RF. These findings suggest that MAA formation and anti‐MAA immune responses could play a role in the transition from subclinical autoimmunity to clinically apparent arthritis.